2020
DOI: 10.1002/ppj2.20002
|View full text |Cite
|
Sign up to set email alerts
|

Phenomic selection and prediction of maize grain yield from near‐infrared reflectance spectroscopy of kernels

Abstract: High-throughput phenotyping technologies, which can generate large volumes of data at low costs, may be used to indirectly predict yield. We explore this concept, using high-throughput phenotype information from Fourier transformed near-infrared reflectance spectroscopy (NIRS) of harvested kernels to predict parental grain yield in maize (Zea mays L.), and demonstrate a proof of concept for phenomic-based models in maize breeding. A dataset of 2,563 whole-kernel samples from a diversity panel of 346 hybrid tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(103 citation statements)
references
References 52 publications
6
63
0
Order By: Relevance
“…Several studies reported the strong correlation between reflectance bands and yield in different crop plants such as alfalfa ( Kayad et al, 2016 ; Feng et al, 2020 ), wheat ( Prey and Schmidhalter, 2019 ), maize ( Lane et al, 2020 ), rice ( Wan et al, 2020 ), and sugarcane ( Verma et al, 2020 ). The visible reflectance bands can be splitted into three main regions, red (650–700 nm), green (495–570 nm), and violet–blue (390–495 nm) ( Hennessy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the strong correlation between reflectance bands and yield in different crop plants such as alfalfa ( Kayad et al, 2016 ; Feng et al, 2020 ), wheat ( Prey and Schmidhalter, 2019 ), maize ( Lane et al, 2020 ), rice ( Wan et al, 2020 ), and sugarcane ( Verma et al, 2020 ). The visible reflectance bands can be splitted into three main regions, red (650–700 nm), green (495–570 nm), and violet–blue (390–495 nm) ( Hennessy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some compounds with similar biosynthetic origins do not share strong correlations. For example, fat, crude fiber and starch are both made from glucose, yet they are negatively correlated ( Figure 3 ), and Lane et al [ 47 ] also reported a very poor correlation between starch and fat (r = <0.17). This negative correlation is likely due to the very different functional roles played by the compounds.…”
Section: Discussionmentioning
confidence: 99%
“…One method to achieve HT analysis of quinoa seed composition is the use of near-infrared (NIR) spectroscopy, in which, in theory, any sample measurement can be predicted as long as the sample’s spectral data are correlated with the desired measurement [ 197 ]. This technology has diverse capabilities, such as phenomic selection and prediction of maize yield from kernels [ 198 ], and has been successfully applied to predict amino acid content in quinoa [ 199 ]. In addition to the NIR methodology, mid-infrared should be considered as a useful technology with practical applications in quinoa.…”
Section: Harvest and Post-harvestmentioning
confidence: 99%